Microstructure, mechanical and corrosion properties of friction stir processed ZE41 Mg alloy. (2019) - Vasu, Ch.; Venkateswarlu, B.; Venkateswara Rao, R.; Chanti, B.; Saikrishna, M.; Ratna Sunil, B.
Abstract: Magnesium based materials have become attractive choice to fabricate degradable bone plates and screws in the field of biomedical engineering. Several advantages such as biocompatibility, non-toxicity, biodegradability, non-allergic and optimum mechanical behavior are the advantages of Mg as an implant material. However, the uncontrolled corrosion is the main limitation of Mg which is being addressed by several routes such as alloying, developing composites, surface coatings and microstructural modification. In the present study, ZE41 Mg alloy has been processed by friction stir process (FSP) to achieve grain refinement. Then the effect of modified microstructrue on mechanical and corrosion behavior was investigated. Metallographic studies showed grain size reduction after FSP from 100 µm to 5 µm. The secondary phase that appeared as interconnected networks at the grain boundary before FSP was observed as dispersed like small discontinuous particles due to FSP. From the hardness measurements, higher values were observed after FSP due to grain refinement and the super saturation of grains. From corrosion experiments, the change in the corrosion rate was observed as insignificant after FSP. Hence the present work suggests adopting FSP as a promising tool to develop grain refined ZE41 Mg alloy for biomedical applications with enhanced mechanical performance without deteriorating the corrosion behavior.